1973
DOI: 10.1007/bf02640838
|View full text |Cite
|
Sign up to set email alerts
|

Analytical critique of hexitols used as a cooking medium

Abstract: Analysis by differential scanning calorimetry and gas liquid chromatography of hexitol blends used as a roasting medium for peanuts demonstrated that there was no significant deterioration of the hexitol components due to prolonged repetitive heating. Small decreases in the hexitol content of the roasting medium, which were found after 72 hr at a temperature of 330 F, closely corresponded to the increases in the hexitan content. Furthermore no evidence could be found of any significant oxidative degradation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1973
1973
2008
2008

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…According to Damy and Jorge [31], Nawar [32], Waltking and Wessels [33], and Tyagi and Vasishtha [34], during the fry process, the oil interacts with the air, the water, and other Fig. 1 Response surface for rhamnose concentration (g/l) as a function of the aeration to agitation ratio after 48 h incubation at 30°C for Pseudomonas aeruginosa PACL growth in waste frying soybean oil components of the food that it is being fried, originating a great diversity of chemical reactions, such as hydrolyzation, oxidation, and polymerization of the triacylglycerol molecule.…”
Section: Comparison Of Biosurfactant Production Using Different Carbomentioning
confidence: 98%
“…According to Damy and Jorge [31], Nawar [32], Waltking and Wessels [33], and Tyagi and Vasishtha [34], during the fry process, the oil interacts with the air, the water, and other Fig. 1 Response surface for rhamnose concentration (g/l) as a function of the aeration to agitation ratio after 48 h incubation at 30°C for Pseudomonas aeruginosa PACL growth in waste frying soybean oil components of the food that it is being fried, originating a great diversity of chemical reactions, such as hydrolyzation, oxidation, and polymerization of the triacylglycerol molecule.…”
Section: Comparison Of Biosurfactant Production Using Different Carbomentioning
confidence: 98%
“…These studies are reported in detail elsewhere (7). Crystalline sorbitol and mannitol, analyzed by gas chromatographic procedures before and after heat treatment of each, at ca.…”
Section: Studies Of Heated Hexitolsmentioning
confidence: 99%